2021
DOI: 10.3390/genes12111747
|View full text |Cite|
|
Sign up to set email alerts
|

m6A mRNA Methylation Regulates LKB1 to Promote Autophagy of Hepatoblastoma Cells through Upregulated Phosphorylation of AMPK

Abstract: The N6-methyladenosine (m6A) RNA modification can regulate autophagy to modulate the growth and development of tumors, but the mechanism of m6A modification for the regulation of autophagy in hepatocellular carcinoma cells (HCC) remains unclear. In the study, the knockdown of the Wilms’ tumor 1-associating protein (WTAP) was made in HCC to study the correlation between m6A modification and autophagy. A fluorescent confocal microscopy analysis showed that the knockdown of WTAP could facilitate the autophagy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…With the development of high-throughput sequencing technology, more and more aberrantly expressed mRNAs have been identi ed in HB [5][6][7]. Moreover, the elevated N6-methyladenosine alteration in HB represents a carcinogenic pathway [8]. Several studies have also found that various genes, such as zinc nger antisense 1 [9] and TUG1 [10], are involved in proliferation, apoptosis, and glutaminolysis.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, more and more aberrantly expressed mRNAs have been identi ed in HB [5][6][7]. Moreover, the elevated N6-methyladenosine alteration in HB represents a carcinogenic pathway [8]. Several studies have also found that various genes, such as zinc nger antisense 1 [9] and TUG1 [10], are involved in proliferation, apoptosis, and glutaminolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study found that WTAP could regulate autophagy by mediating the phosphorylation of the positive autophagy regulator, AMPK, in HCC cells ( Li G. et al, 2021 ). Mechanistically, WTAP decreased the mRNA stability of Lkb1 , the kinase upstream of AMPK which regulates AMPK phosphorylation, in an m 6 A-dependent manner ( Li G. et al, 2021 ). Subsequently, knockdown of Wtap resulted in increased autophagy ( Li G. et al, 2021 ).…”
Section: The Role Of M 6 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…Mechanistically, WTAP decreased the mRNA stability of Lkb1 , the kinase upstream of AMPK which regulates AMPK phosphorylation, in an m 6 A-dependent manner ( Li G. et al, 2021 ). Subsequently, knockdown of Wtap resulted in increased autophagy ( Li G. et al, 2021 ).…”
Section: The Role Of M 6 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…In addition, WTAP knockdown led to a G2/M phase block in hepatocellular carcinoma via the ETS1-p21/p27 axis, promoting apoptosis in tumor cells [ 53 ]. WTAP knockdown inhibited hepatocellular carcinoma growth and metastasis in hepatocellular carcinoma by promoting autophagosome production [ 105 ]. Further mechanistic studies revealed that liver kinase B1 (LKB1), the upstream kinase of Adenosine 5′-monophosphate activated protein kinas (AMPK), is regulated by WTAP and mediates AMPK phosphorylation in an m 6 A-dependent manner, thereby promoting hepatocellular carcinoma autophagy [ 105 , 106 , 107 ].…”
Section: Role Of Wtap In Carcinogenesismentioning
confidence: 99%